Gut microbiota-derived metabolite trimethylamine-N-oxide and stroke outcome: a systematic review - Zhang, Peng; Wang, Rui; Qu, Yang; Guo, Zhen-Ni; Yang, Yi (Frontiers in Molecular Neuroscience, 2023)
Introduction: The relationship between baseline trimethylamine N-oxide (TMAO) levels and stroke outcomes remains unclear. Therefore, this systematic review aimed to summarize the existing relevant research. Methods: We searched for studies on the association between baseline plasma levels of TMAO and stroke outcome in the PubMed, EMBASE, Web of Science, and Scopus databases from their inception to October 12, 2022. Two researchers independently reviewed the studies for inclusion and extracted the relevant data. Results: Seven studies were included in the qualitative analysis; among them, six and one studies reported the outcome of acute ischemic stroke (AIS) and intracerebral hemorrhage (ICH), respectively; further, no study reported the outcome of subarachnoid hemorrhage. Among patients with AIS, high baseline TMAO levels were associated with unfavorable functional outcomes or mortality at 3 months, as well as high hazard ratio of mortality, recurrence, or major adverse cardiac event. Moreover, TMAO levels showed predictive utility for unfavorable functional outcomes or mortality at 3 months. Among patients with ICH, high TMAO levels were associated with unfavorable functional outcomes at 3 months, regardless of whether the TMAO value was considered as a continuous or categorical variable. Conclusion: Limited evidence indicates that high baseline plasma levels of TMAO may be associated with poor stroke outcomes. Further studies are warranted to confirm the relationship between TMAO and stroke outcomes.